Impulsivity and Depressive Brooding in Internet Addiction: A Study With a Sample of Italian Adolescents During COVID-19 Lockdown - Diotaiuti, Pierluigi; Girelli, Laura; Mancone, Stefania; Corrado, Stefano; Valente, Giuseppe; Cavicchiolo, Elisa (Frontiers in Psychiatry, 2022)
This contribution presents a study conducted on a sample of Italian adolescents (n = 411) in the period of the first Covid-19 lockdown. The study investigated the role and predictive weight of the impulsivity and depressive brooding variables on Internet addiction, using a hierarchical regression analysis. The participants were administered the Uso-Abuso e Dipendenza da Internet [Internet Use-Abuse and Addiction] (UADI-2), the Barratt Impulsiveness Scale-11 (BIS-11) and the Ruminative Response Scale (RRS). In terms of percentage distribution, 28% of the participants were in the full dependency range, while 34.7% demonstrated Internet abuse behaviour. The results highlighted not only the predictive value of impulsiveness (β = 0.323) and ruminative thinking (β = 0.258), but also the role of gender (β = -0.205) on Internet addiction. Thus, male participants showed higher levels of Internet addiction, with higher scores on impulsiveness and brooding way of thinking. The study shows that the issue in question is significantly present among adolescents; in addition, not only targeted awareness programmes but also psycho-educational and clinical interventions to promote greater emotional and cognitive control would be necessary as a preventive and mitigating measure. Psychological interventions can help increase self-awareness, develop emotional regulation and impulse control, and correct maladaptive cognitions which in adolescents are mostly driven by a ruminative cognitive style.